2017
DOI: 10.7602/jmis.2017.20.4.143
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Hand-Assisted Laparoscopic Surgery for Colorectal Disease in an Emergency Setting

Abstract: Purpose: Laparoscopic surgery is accepted as a standard alternative to open procedures in the management of both benign and malignant colorectal disease. However, the safety and efficacy of the laparoscopic approach for emergency colorectal surgery has not been established. Hand-assisted laparoscopic (HAL) surgery might be a suitable option for colectomy in an emergency setting. The aim of this study was to report our experience of emergency HAL colectomy. Methods:This was a retrospective review of consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Recent evidence demonstrated laparoscopic resections for complicated diverticular disease (Hinchey I‐III) to be feasible with encouraging outcome . For obstructing colorectal cancer, laparoscopic approach was linked to shorter length of stay and reduced mortality . Despite an expected lower overall ERAS compliance in the urgent setting (32% of patients with >70% ERAS compliance), ERAS has been adopted as routine care pathway and associated with benefits in the present institution and by others …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence demonstrated laparoscopic resections for complicated diverticular disease (Hinchey I‐III) to be feasible with encouraging outcome . For obstructing colorectal cancer, laparoscopic approach was linked to shorter length of stay and reduced mortality . Despite an expected lower overall ERAS compliance in the urgent setting (32% of patients with >70% ERAS compliance), ERAS has been adopted as routine care pathway and associated with benefits in the present institution and by others …”
Section: Discussionmentioning
confidence: 99%
“…Unfavourable patient‐ and disease‐related conditions in patients needing emergency colectomy go along with increased postoperative complication rates . Nevertheless, recent data showed primary resection as valid option for complicated diverticulitis or obstructive colon cancer, with further benefits through laparoscopic approach in selected cases . Tailored enhanced recovery protocols turned out to be feasible and beneficial even for urgent indications .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found similar disease specific survival for elderly and young colorectal cancer patients [28][29][30][31] , but difference in overall survival; this means that the increase of mortality in oncogeriatric patients is due to competing causes of death and not to CRC. Consequently decreased survival in the elderly is mainly due to differences in early mortality [28,[32][33][34][35][36] .…”
Section: Surgical Techniques and Outcomesmentioning
confidence: 94%
“…Consequently decreased survival in the elderly is mainly due to differences in early mortality [28,[32][33][34][35][36] . Some authors showed that time between admission and surgery doesn't increase morbidity and mortality rates [29] ; others, demonstrated that delays in performing emergency surgery in elderly patients leads to higher complication rates [3,30] .…”
Section: Surgical Techniques and Outcomesmentioning
confidence: 99%
“…7 HALS is the one of the approach methods of minimally invasive surgeries; it also has better short-term benefit when compared to conventional open surgery. But there few studies which compare the HALS and open surgery.…”
Section: Editorialmentioning
confidence: 99%